Implementation of the acquis communautaire in EU candidate countries: A reappraisal - Dorian Jano (Europa-Kolleg Hamburg, Institute for European Integration, 2012)
This article replicates and extends the Hille and Knill (2006) study on the implementation of the acquis communautaire in EU candidate countries. We use a different methodological approach, i.e. the fuzzy set qualitative comparative analysis (fsQCA), and extend the analysis by incorporating EU-level factors (the intensity of EU conditionality). The fsQCA analysis shows that the bureaucratic effectiveness is systematically related to candidate countries' alignment performance whereas there is no systematic relationship between alignment performance, political constraints, financial capacities, government membership support and/or the absence of intensity of EU conditionality.
Keywords: 320; acquis communautaire; EU candidate countries; Central and Eastern Europe; enlargement; Europeanization; fuzzy set qualitative comparative analysis; implementation; policy change